The dark side of romantic jealousy. (1st September 2017) - Chin, Kristi; Atkinson, Breanna Ellen; Raheb, Hana; Harris, Elizabeth; Vernon, Philip A.
Abstract: The present study investigates whether self-esteem and entitlement moderate the relation between jealousy (cognitive, emotional, behavioral) and the Dark Triad (narcissism, Machiavellianism, psychopathy). To test this question, 453 participants (311 females, 140 males, 2 unidentified) between the ages of 17 to 81 years (M = 33.19, SD = 10.32) completed the Multidimensional Jealousy Scale, the Short-D3, the Psychological Entitlement Scale, and the Rosenberg Self-Esteem Scale. The interaction of self-esteem and Machiavellianism has an effect on cognitive jealousy and emotional jealousy, and the interaction of selfesteem and narcissism has an effect on behavioral jealousy. The interaction of entitlement and narcissism has an effect on emotional jealousy and behavioral jealousy, and the interaction of entitlement and psychopathy has an effect on cognitive jealousy. These findings identify dimensions of the Dark Triad and other personality traits that influence the propensity to experience different types of jealousy. Highlights: Two studies investigating relations between the Dark Triad and jealousy. Study 1 reports correlations between these variables. Study 2 replicates Study 1 and expands by looking at moderator variables. Results of the 2 studies contribute to the literature on the Dark Triad.